Neoadjuvant oncogene-targeted therapy in early stage non-small cell lung cancer as a strategy to improve clinical outcome and identify early mechanisms of resistance - McCoach, Caroline E. (Clin Lung Cancer, 2016)
Evaluations of resistance mechanisms to targeted treatments in non-small cell lung cancer (NSCLC) are necessary for development of improved treatment after progression and to help delay progression. Populations of cells that survive after initial treatment form the basis of resistance via outgrowth of resistant clones or activation of alternative signaling pathways. Here we describe a clinical trial approach in which patients with EGFR, ALK, ROS1 and MET exon 14 alterations and early stage (IA–IIIA) NSCLC will be treated with induction epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) or crizotinib, a TKI which inhibits anaplastic lymphoma kinase (ALK), ROS proto-oncogene 1 (ROS1) and hepatocyte growth factor receptor (MET). We will evaluate resected tumor samples for pathologic response to induction therapy, overall response rate and disease free survival. Additionally, we will assess patients for early evidence of resistance to targeted therapy in terms of activation of alternative signaling pathways and for identification of resistance clones in remnant cell populations.